The Role Of The Production Budget As a Management Tool In Supporting Production Effectiveness (Case Study At PT. Indofood CBP Sukses Makmur Tbk 2019-20220) - Gabriel Armando Sormin; Dian Hakip Nurdiansyah (STIE Amkop Makassar, 2023)
PT Indofood CBP Sukses Makmur Tbk is headquartered in Jakarta, Indonesia, as a producer of various types of food and beverages. We can see from the current phenomenon or problem, many factors affect the decline in sales of a company, therefore this study aims to determine the effect of raw material costs on net sales that occur at PT Indofood CBP Sukses Makmur Tbk. Production budgets are made to control these costs, which originated from the budget-making sales to Raw Material Cost budget, Direct Labour Cost budget, and Overhead Cost budget. By comparing the budget with the realization, management can know when a deviation occurs and whether the deviation is harmful or beneficial to the company. The company set a tolerance limit of 5% deviation. Making the production budget is useful for management as a tool in supporting the cost-effectiveness of production. Production costs can be said to be effective, if there is a favorable difference of the cost of the actual standard. In 2019 raw materials cannot be said to be effective, because there are differences that are unfavorable, due to price differences that are controlled by the market price. Difference Direct Labour Cost unfavorable because of the large total production depending on market demand. Favorable differentiation of Overhead Cost in 2019 and 2020 reflected that the Overhead Cost has been effective and can be controlled by the company. Overall, the company experienced a favorable difference in production costs so it can be said effectively, but the company needs to pay more attention to the price of raw materials and direct labor costs that have not been restrained because of unprofitable differentiation.